Enhancement of charge transport properties of small molecule semiconductors by controlling fluorine substitution and effects on photovoltaic properties of organic solar cells and perovskite solar cells. Issue 11 (27th July 2016) - Yun, Jae Hoon; Park, Sungmin; Heo, Jin Hyuck; Lee, Hyo-Sang; Yoon, Seongwon; Kang, Jinback; Im, Sang Hyuk; Kim, Hyunjung; Lee, Wonmok; Kim, BongSoo; Ko, Min Jae; Chung, Dae Sung; et al.
Abstract : Effects of fluorine substitution of small molecular semiconductor on charge transport and photovoltaic properties are systematically studied. Abstract : We prepared a series of small molecules based on 7, 7′-(4, 4-bis(2-ethylhexyl)-4 H -silolo[3, 2- b :4, 5- b ′]dithiophene-2, 6-diyl)bis(4-(5′-hexyl-[2, 2′-bithiophene]-5-yl)benzo[ c ][1, 2, 5]thiadiazole) with different fluorine substitution patterns (0F–4F ). Depending on symmetricity and numbers of fluorine atoms incorporated in the benzo[ c ][1, 2, 5]thiadiazole unit, they show very different optical and morphological properties in a film.2F and4F, which featured symmetric and even-numbered fluorine substitution patterns, display improved molecular packing structures and higher crystalline properties in a film compared with1F and3F and thus, 2F achieved the highest OTFT mobility, which is followed by4F . In the bulk heterojunction solar cell fabricated with PC71 BM, 2F achieves the highest photovoltaic performance with an 8.14% efficiency and0F shows the lowest efficiency of 1.28%. Moreover, the planar-type perovskite solar cell (PSC) prepared with2F as a dopant-free hole transport material shows a high power conversion efficiency of 14.5% due to its high charge transporting properties, which were significantly improved compared with the corresponding PSC device obtained from0F (8.5%). From the studies, it is demonstrated that low variation in the local dipole moment and the narrow distribution of2F conformers make intermolecular interactions favorable, which may effectively drive crystal formations in the solid state and thus, higher charge transport properties compared with1F and3F .